Membaca Pemikiran Orang Jawa Tentang Kesempurnaan Hidup Melalui Teks Piwulang - Pristia Nugroho, Akbar; Edy Nugroho, Yusro (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The Serat Piwulang Kasampurnaning Ngagesang manuscript is one of the Javanese manuscripts that contains the teachings of life. This manuscript is important to study because it contains teachings to achieve perfection in life according to Javanese thinking. The problem in this study is that the Javanese people's thoughts about the perfection of life contained in this manuscript have not been revealed. The purpose of the research is to explore the thoughts of the Javanese people from the source of the text of Serat Piwulang Kasampurnaning Ngagesang which then the results of the description can be known to the general public and can be used as a guideline for the younger generation. This study uses an objective approach, with heuristic and hermeneutic reading models. Heuristic reading is carried out by reading the entire text sourced from the NB 807 manuscript of the National Library of the Republic of Indonesia. Hermeneutic reading is carried out by paying attention to textual, historical and philosophical meanings. The results of the study show that there is a view of the importance of names for human life and the seven things that are desired in life. Javanese people view the name as something important because it is an honor for everyone. Perfection of life for Javanese people is the fulfillment of seven desired things consisting of health and safety, food, shelter, clothing, honor or power, security and peace of mind, sincerity and sustainability. And the key to getting these seven things is to be grateful, patient, praying, and trying. All of it comes from the heart of each one. The heart can have taste, but the taste does not have the heart.